Hittite mi-e-nu-us: Humans as ‘meek’ or ‘lesser’ - Puhvel, Jaan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
A recent article posits Hittite mi-e-nu- as ‘male’, hapax (KBo 3.28 II 16) also ‘human being’, with abundant cognates all the way to English ‘man’, with strained and forced recastings of mi-e-nu- ’soft, mild’ in all other passages as ‘male’. Here crucial KBo 3.28 II 14-16 is reamended and retranslated, implicitly declining the article’s assumptions and conclusions, affirming the vocable involved as formulaic of ‘human frailty’ in binary contrast to divine powers.